Serial analysis of ESR1 mutations in cell-free DNA from hormone receptor-positive, HER2-negative metastatic breast cancer during palliative endocrine therapy - Baek, Soo Yeon; Hong, Meehyang; Lee, Seungah; Joo, Seulgi; Jang, JungPil; Jung, Chinkoo; Lee, Hyein; Yoo, Tae-Kyung; Chung, Il Yong; Kim, Hee Jeong; Ko, Beom Seok; Lee, Jong Won; et al. (Frontiers in Oncology, 2026)
BackgroundActivating mutations in ESR1 gene are a known mechanism of endocrine resistance. We analyzed ESR1 mutations in cell-free DNA (cfDNA) from serially collected blood from hormone receptor-positive, human epidermal growth factor receptor 2-negative metastatic breast cancer patients to investigate their impact on outcomes.MethodsA total of 268 cfDNA samples serially collected from 25 patients who underwent palliative endocrine therapy were examined. Seven ESR1 hotspot mutations were tested in cfDNA using droplet digital polymerase chain reaction. Progression-free survival (PFS) was analyzed using the Kaplan–Meier method. Blood ESR1 mutation (bESR1) results were correlated with clinical response.ResultsAmong 25 patients, baseline bESR1 mutation was negative for all patients (0/4) and 64.0% (16/25) was bESR1-positive at any time. bESR1 positivity did not affect PFS. Those whose bESR1 cleared in subsequent cfDNA exhibited longer PFS. Among patients with clinical progression, 57.1% (8/14) were bESR1-positive, and four had bESR1 detected before clinical progression.ConclusionsWe observed worse outcomes in patients with persistent bESR1 detection during first-line endocrine therapy and then sustained positive. bESR1 was detected prior to clinical progression in half of patients. Our study suggests the benefit of bESR1 monitoring during palliative endocrine therapy.